The role of brand image and customer commitment in mediating service quality towards customer loyalty - Mahatama, Anak Agung Bagus Putra; Wardana, Made (International research journal of management, IT and social sciences, 2021)
The purpose of this study is to explain the role of brand image and customer commitment in mediating the effect of service quality on customer loyalty. The population in this study is customers at Kedonganan Village Credit Institution. The purposive sampling method has been used with 130 respondents included. Questionnaires were distributed and the result are analyzed using PLS (Partial Least Square) technique. The results of this study indicate that service quality has a positive and significant effect on brand image, customer commitment, and customer loyalty at Kedonganan Village Credit Institution. There was a significant role of brand image and customer commitment in mediating the effect of service quality on customer loyalty at Kedonganan Village Credit Institution. In order to improve brand image and customer commitment, it is hoped that Kedonganan Village Credit Institution will be able to provide faster service, attractive promotions, and technology improvement to encourage customer loyalty.